Proteomic analysis of phosphorylation in cancer. (June 2014) - Ruprecht, Benjamin; Lemeer, Simone
<x xml:space="preserve">Abstract</x> Constitutive activity of kinases is known to be crucial for a tumor to maintain its malignant phenotype, a phenomenon which is often referred to as oncogene addiction. The in-depth analysis of aberrant signaling pathways by the analysis of protein phosphorylation has become feasible through recent advances in proteomics technology. In this article we will review developments in the field of phosphoproteomics and its application in cancer research. The most widely used technologies for the generic enrichment of phosphopeptides are discussed as well as targeted approaches for the analysis of a specific subset of phosphopeptides. Validation experiments of phosphorylation sites using targeted mass spectrometry are also explained. Finally, we will highlight applications of phosphoproteomic technology in cancer research using cell lines and tissue.